Sistem Pendukung Keputusan Pemilihan Staf Keamanan Terbaik Hotel Menggunakan Metode SMARTER - Surizar Rahmi Danur; Nirwan Sinuhaji; Alyiza Dwi Ningtyas; Donny Sanjaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The hotel industry provides accommodations that focus on guest comfort and safety. One crucial aspect of maintaining hotel security is selecting qualified security staff. However, the hotel faces challenges due to a lack of prior security staff selection. This results in difficulties in establishing clear selection criteria, resulting in an inefficient and unprofessional selection process. To address this issue, a decision support system (DSS) is required. This system will assist in data management, value calculation, and the generation of informed decisions. With a DSS, decision-making becomes easier, faster, and more accurate. This will increase efficiency, professionalism, and reliability in the security staff selection process. Furthermore, the best security staff will be given incentives for a period as a reward for the quality of their work. Implementing a DSS allows the selection of the best security staff based on predetermined criteria. The SMARTER (Simple Multi-Attribute Rating Technique Exploiting Ranks) method can be used as a tool in a DSS to select the best security staff. Using the SMARTER method can solve the problem of selecting the best security staff. Aripin, with a score of 0.87, was selected as the best security staff. This will help the hotel maintain guest trust, provide a sense of security and comfort, and build a positive reputation. As a result, it will become more professional in managing hotel security and providing excellent guest service.